Bendix MA-015 Differential Pumping System - Bendix Corporation (1970)
Four general views of the exterior and interior of a Bendix Model MA-015 Differential Pumping System and assorted control panels for various accessories attached to a Bendix Model MA-02 Time-of-Flight Mass Spectrometer system. Components visible in the photographs include an oscilloscope, variable oscillator, ion source, and vacuum system, as well as a control panel for an ionization gauge. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Oscilloscopes; Scientific apparatus and instruments; Mass spectrometers; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Spectrometer industry